Hubungan Pola Konsumsi Jajanan dan Aktivitas Fisik Dengan Obesitas Pada Remaja di SMP N 1 Kuta - Yanti, Ni Kadek Dea Widya; Dewantari, Ni Made; Sukraniti, Desak Putu (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Obesity is one of the nutritional problems caused by the accumulation of fat in the body and the consumption of food that exceeds the needs. Consumption of various types of snacks containing high sugar and high fat and lack of physical activity affect the incidence of obesity. The purpose of this study was to determine the relationship between snacks consumption patterns and physical activity with obesity in adolescents at SMPN 1 Kuta. This type of research is observational with a cross sectional design conducted in December 2022 which amounted to 90 people by simple random sampling. Data on snacks consumption patterns were collected through interviews with the SQ-FFQ form. Physical activity data using the PAQ-C questionnaire. Data analysis in the form of the relationship between snack consumption patterns and physical activity with obesity using the Pearson correlation test. There is a relationship between the type of snack consumption and obesity (p=0.000). There is a relationship between frequency of snack consumption and obesity (p=0.004). There is a relationship between energy snacks with obesity (p=0.000) and there is a relationship between physical activity with obesity (p=0.000). It is recommended that schools and parents pay more attention to the selection of snacks consumed and conduct regular monitoring of nutritional status in school adolescents.